Identity and naming practices in British marriage and civil partnerships - Jones, Lucy; Mills, Sara; Paterson, Laura L.; Turner, Georgina; Coffey-Glover, Laura (Equinox Publishing, 2016)
This article demonstrates the continued prevalence of traditional, heteronormative practices regarding marriage and naming practices in Britain, and also considers the complex choices made by same-sex couples who marry in relation to whether there are any benefits in changing their surname. The study draws on data from an online survey of 1,000 UK respondents, and reveals that it continues to be viewed as more ‘normal’ for a woman to take her husband’s surname in a heterosexual union than for her to make any other choice. Whilst other options (such as the woman retaining the surname given to her by her parents, for instance) are often considered in relation to heterosexual marriage, these continue to be seen as a deviation from the norm. We find that the role of tradition is critical to heterosexual women’s decisions over what to do with their surname, whether they follow the culturally expected route or consciously deviate from it. Same-sex couples are broadly perceived to have comparably more freedom than heterosexuals regarding their names, and here we analyse whether this is the case. Through qualitative critical analysis of the discursive responses of those completing our survey, and some quantitative discussion of the data, we demonstrate that heteronormative assumptions about a woman’s role in a heterosexual relationship have continued salience and that this leads to a conscious and often difficult negotiation of her own identity as both an individual and a wife.